Pendampingan UMKM Penjahit Berbasis Teknologi Digital dalam Perspektif Industri Kreatif di Bogor Utara - Asep Saepulrohman; Layung Paramesti Martha; Putri Nabila Adinda Adriansyah; Leny Heliawati (Jurnal Pemberdayaan Masyarakat, 2023)
Tailoring Micro, Small and Medium Enterprises (MSMEs) or often called Tailors experienced an extraordinary economic downturn during the Covid-19 pandemic. Convection innovation as a form of existence in the midst of a pandemic outbreak that still exists today to survive must carry out various kinds of creativity. One of them is digitizing the marketing system, updating fashion trends, increasing relationships, providing the best service, collaborating with agencies, and others. In this service the focus is on digitizing the system and developing the concept of relations using the graph theory concept to increase competitiveness. The location of the service will be focused on one of the tailors, namely Sarinah Tailor in Kedunghalang Village, North Bogor District.